2022
DOI: 10.1002/batt.202200182
|View full text |Cite
|
Sign up to set email alerts
|

An Aluminum‐Benzo[1,2‐b:4,5‐b’]dithiophene‐4,8‐dione Organic Rechargeable Battery Featuring Low Self‐Discharge

Abstract: The achievable cell-level specific energy density of existing aluminum-ion batteries (AIBs) employing AlCl 4À intercalation type cathodes is intrinsically limited by the chloroaluminate anolyte. Towards achieving AIBs with higher specific energy, it is imperative to explore alternative cell chemistries that fundamentally tap the capacity of Al metal anode. Here, we report a benzo[1,2-b:4,5-b']dithiophene-4,8-dione (BDTD) organic electrode material with favorable AlCl 2 + intercalation mecha-nism. This BDTD cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Meanwhile, b = 1 indicates non-diffusion-controlled capacitive behavior. 46 Besides, the b-values for anodic and cathodic peaks were 0.79 and 0.80, respectively, (Fig. 7c), suggesting that the diffusion and capacitive behaviour were almost equal.…”
Section: Resultsmentioning
confidence: 90%
“…Meanwhile, b = 1 indicates non-diffusion-controlled capacitive behavior. 46 Besides, the b-values for anodic and cathodic peaks were 0.79 and 0.80, respectively, (Fig. 7c), suggesting that the diffusion and capacitive behaviour were almost equal.…”
Section: Resultsmentioning
confidence: 90%
“…Anthraquinone organic compounds have shown good electrochemical activity, anthraquinone derivatives also contain carbonyl sites (C=O) to achieve ion storage. Wang et al [63] reported a benzo[1,2-b:4,5-b']dithiophene-4,8-dione (BDTD) organic cathode material with an elongated plate-like morphology (Figure 11a,b). The separator was modified by conductive carbon Super P to alleviate the accidental shuttle of soluble BDTD species and improve the overall conductivity of the battery.…”
Section: Quinonesmentioning
confidence: 99%
“…Anthraquinone organic compounds have shown good electrochemical activity, anthraquinone derivatives also contain carbonyl sites (C=O) to achieve ion storage. Wang et al [63] . reported a benzo[1,2‐b:4,5‐b’]dithiophene‐4,8‐dione (BDTD) organic cathode material with an elongated plate‐like morphology (Figure 11a,b).…”
Section: Research Progress Of Aluminum‐organic Batteriesmentioning
confidence: 99%
See 2 more Smart Citations